DIFFERENCES OF PLANTING MEDIA AND CONCENTRATION OF ONION (Allium ascalonicum L) EXTRACT TOWARDS BODY GUAVA CITRA (Syzygium aquenum Burn) - Lukman; Salawati; Sjarifudin Ende (International Journal of Social Science, 2022)
This study aims to determine the effect of planting media and onion extract concentration on the growth of guava image cuttings using a factorial RAK consisting of 12 treatment combinations, namely: T0B1 = Soil with 17% extract, T0B2 = Soil with 33% extract, T0B3 = Soil with 50% extract, T1B1 = 3 kg Mixed soil 1 kg sand with 17% extract, T1B2 = 3kg Soil mixed 1 kg sand with 33% extract, T1B3 = 3 kg Soil mixed 1 kg sand with 50% extract, T3B1 = 3 kg Soil mixed with fertilizer 1 kg with 17% extract, T3B2 = 3 kg Soil mixed with fertilizer 1 kg with extract 33%, T3B3 = 3 kg Soil mixed with fertilizer 1 kg with extract 50%. Each treatment was repeated 3 times so that there were 36 polybags. The results of this study showed that in observing the number of shoots the best-growing media treatment was T0 at the age of 6 WAP (4.33) and 7 WAP (4.56), the best concentration of onion extract was treatment B1 at 6 WAP (3,50) and 7 WAP (4,67), observing the number of roots with the best treatment B1 at the age of 8 WAP (3.00), observing the number of roots with the best B1 at the age of 8 DAP (3,96). There was no interaction between the growing media and onion extract.